مسندِ حارثی کے رجال پر ائمہ جرح وتعدیل کے اشکالات اور ان کے جوابات: ایک تحقیقی جائزہ: The Criticisms of the Hadith Scholars on the Narrators of Musnad al-Hārithī and Their Responses (Al-Aasar, 2025)
This research examines the narrators of Musnad al-Imām al-Aʿẓam compiled by al-Ḥārithī, focusing on the critical evaluations of hadith scholars regarding their reliability. The Musnad holds a significant position among the early sources that transmit the narrations of Imām Abū Ḥanīfa; however, several narrators within its chains have been subject to severe criticism. Some were accused of fabricating hadiths, lying, or having weak memory, while others were regarded as truthful and trustworthy. The study begins with an overview of the science of al-jarḥ wa al-taʿdīl (criticism and accreditation of narrators), followed by an introduction to al-Ḥārithī and his Musnad. It then investigates in detail the major controversial narrators such as Aḥmad b. ʿAbd Allāh al-Kindī, Yūnus b. Bukayr, ʿAbd Allāh b. Wāqid al-Ḥarrānī, Shuʿayb b. Ayyūb, Nuʿaym b. Ḥammād, Abū Muqātil Ḥafṣ b. Sulaym, and Muqātil b. Sulaymān. The study presents the statements of hadith critics, analyzes the causes of their judgments, and provides scholarly responses to these objections. The findings indicate that while some reports in the Musnad are weak or unreliable, a considerable portion is transmitted through trustworthy narrators and thus remains valid for use. This research highlights the methodological differences among the hadith critics and concludes that the acceptance or rejection of narrators requires a detailed, case-by-case evaluation rather than sweeping generalizations.